A Place at the Table? Parliamentary Committees, Witnesses and the Scrutiny of Government Actions and Legislation. Issue 1 (13th February 2019) - Bochel, Hugh; Berthier, Anouk
Abstract : Issues of diversity in elected bodies have been highlighted in recent years, both with regard to elected representatives themselves, and, more recently, in respect of the treatment of those working in such institutions, especially women. This article focuses on another aspect of diversity, inequality and representation, the voices heard by parliamentary committees in their scrutiny of government actions and legislation. The article discusses the current position in the Scottish Parliament (and other UK legislatures) with, for example, around three-fifths of witnesses at Holyrood being male, and highlights both 'demand' and 'supply' factors that influence the make-up of committee witnesses. It also identifies a number of functions that witnesses can play for committees, and how these relate to diversity and representation, and suggests that there may be benefits to committees and legislatures in hearing from a wider range of voices.